Preparation method of dication positive electrode material
By using heteropolyblue lithium sodium and porous structure conductive polymer in the positive electrode material of mixed lithium sodium ion battery, the dual cationic positive electrode material was prepared, which solved the shortcomings of existing materials in terms of magnification and cycling performance, and improved safety and gram capacity retention rate.
Patent Information
- Application Number
- CN202411182383.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-02-21
AI Technical Summary
The existing positive electrode materials of mixed lithium sodium ion batteries are still unable to compare with lithium ion batteries in terms of electrical performance such as magnification and circulation, and have a long thermal runaway time and insufficient safety performance.
The skeleton structure of heteropoly acid anion is maintained through the form of heteropoly blue lithium sodium, and the porous structure of the conductive polymer is improved ionic conductivity, and a bicationic positive electrode material is prepared. This method allows both lithium and sodium ions to be transported in the material, improving the magnification and cycling characteristics of the material, and improving safety.
The improvement of the magnification and circulation characteristics of the bication cation cathode material is achieved, while improving safety performance. The capacity retention rate of gram is still above 96% after 50 cycles.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical power sources, and in particular to a method for preparing a dual cation positive electrode material. Background Art
[0002] Currently, the most widely used power battery and energy storage battery is lithium-ion battery. Lithium resources are relatively scarce in my country and mainly rely on imports. Sodium resources are mainly extracted from seawater and the resources are not limited. Therefore, the research and development of sodium ions has increased rapidly in recent years. However, the performance of pure sodium-ion batteries cannot be compared with that of lithium-ion batteries, especially the rate and cycle electrical properties. However, the thermal runaway of sodium-ion batteries takes a longer time and the safety performance is better than that of lithium-ion batteries. Therefore, how to combine the performance advantages of the two has become a current research hotspot.
[0003] The structure of hybrid lithium-sodium ion batteries is similar to that of lithium-ion batteries. They are mainly composed of four main materials: positive electrode, negative electrode, electrolyte, and separator, as well as some auxiliary components. The performance of the positive electrode material largely determines the electrochemical performance of the hybrid lithium-sodium ion battery. Since it needs to have the ability to store lithium ions and sodium ions at the same time, higher requirements are placed on the materials. Therefore, the positive electrode material of the hybrid lithium-sodium ion battery is still the key to restricting the development of this system.
[0004] The invention patent application with patent publication number CN116741945A discloses a positive electrode active material, a positive electrode sheet including the positive electrode active material, and a hybrid lithium sodium ion battery. After a polyanion material is mixed with a Prussian blue material, the polyanion can be embedded in the cubic block gaps of the Prussian blue. At the same time, the higher theoretical density of the polyanion can improve the compaction density of the positive electrode of the hybrid lithium sodium ion battery, which is beneficial to improving the energy density of the hybrid lithium sodium ion battery.
[0005] This patent starts from the perspective of compaction density and improves the energy density of the battery, but energy density is only one of the battery performance parameters. In addition to energy density, battery performance also includes: rate, cycle and other characteristics. Compared with energy density, electrical performance parameters such as rate and cycle can better reflect the comprehensive performance of the battery. Therefore, only improving energy density cannot improve the overall performance of the battery. Summary of the invention
[0006] In order to overcome the defects of the prior art, the present invention provides a method for preparing a dual-cation positive electrode material. In the present invention, the skeleton structure of the heteropolyacid anion is still maintained through the form of heteropoly blue lithium sodium, and the skeleton structure can ensure that both lithium ions and sodium ions can be transmitted in its skeleton; and the conductive polymer prepared by this method has a porous structure, and the sodium ions have a larger radius and can be transmitted through its pores, so the ionic conductivity of the heteropoly blue lithium sodium can be improved to a certain extent.
[0007] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows: A method for preparing a dual cation positive electrode material comprises the following steps: 1) preparing a conductive polymer monomer aqueous solution and a heteropoly acid aqueous solution; 2) electrolyzing the heteropoly acid aqueous solution in step 1) to obtain a heteropoly blue solution of heteropoly acid; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 1:0.5-2, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 1:0.5-2; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess amount of a strong oxidizing acid solution to the mixture in step 4) while stirring, and reacting the mixture at 140°C-180°C for 16h-24h after the addition is complete; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The mass concentration of the conductive polymer monomer aqueous solution in step 1) is 5%-10%; In step 1) H3PW 12 O 40 The molar concentration of the aqueous solution is 0.5mol / L-1mol / L; The electrolysis conditions in step 2) are as follows: the cathode potential is -0.5V to -0.8V, and the electrolysis time is 3-5 hours; The standing time in step 3) is 7-10 days; In the step 1), the conductive polymer monomer is one or more of aniline, thiophene and pyrrole.
[0008] In step 3), the heteropoly acid is H3PW 12 O 40 or H3PMO 12 O 40 ; In the step 3), the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 1.5-2.5:1; The strong oxidizing acid in step 5) is nitric acid, permanganic acid or dichromic acid; The mass concentration of the strong oxidizing acid dilute solution in step 5) is 10%-15%; Beneficial effects of the present invention: 1. The lithium ions and sodium ions in the positive electrode material prepared in the present invention can both participate in ion transport, and it is a dual-cation positive electrode material, which takes into account the rate and cycle characteristics of lithium ion positive electrode materials, and has a certain degree of improvement in safety; the morphology of heteropoly blue lithium sodium in the present invention still maintains the skeleton structure of heteropoly acid anions, and the skeleton structure can ensure that both lithium ions and sodium ions can be transported in its skeleton; and the conductive polymer prepared by this method has a porous structure, and sodium ions with a large radius can be transported through its pores, so the ionic conductivity of heteropoly blue lithium sodium can be improved to a certain extent.
[0009] 2. In the present invention, the conductive polymer has a strong electronic conductivity, and the heteropoly acid is compounded with it, which helps to improve the electronic conductivity of the positive electrode material.
[0010] 3. In the present invention, the heteropoly acid itself has a strong oxidizing property. If it is not electrolyzed into heteropoly blue, its own oxidizing property will directly oxidize and polymerize the polymer monomers added subsequently. The generated substance is a composite state of a conductive polymer and a heteropoly acid salt, which is prone to pore blocking, affecting the material's gram capacity and cycle properties. The role of electrolysis is to allow the heteropoly acid to obtain electrons and become heteropoly blue, which loses its oxidizing characteristics and will not cause pore blocking in subsequent reactions.
[0011] 4. In the present invention, the dilute solution of strong oxidizing acid oxidizes and polymerizes the conductive polymer monomer into a conductive polymer, and during the polymerization process, the hydrogen ions in the acid react with the carbonate ions in the solution to generate carbon dioxide. During the overflow of carbon dioxide, the conductive polymer forms a porous structure. The porous structure is more conducive to the transmission of cations due to its abundant pores, and can improve the transmission rate of cations in the positive electrode material. DETAILED DESCRIPTION
[0012] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0013] Example 1 This embodiment provides a method for preparing a dual cation positive electrode material, comprising the following steps: 1) Prepare 5% aniline aqueous solution and 0.5 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.5 V, and the electrolysis time was 3 hours to obtain H3PW 12 O 40 of heteropoly blue solution; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 2:1, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing for 7 days; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 2:1, and the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 1.5:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess of 10% diluted nitric acid to the mixture in step 4) during stirring, and placing the mixture at 140° C. for reaction for 16 hours after the addition is completed; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0014] Example 2 This embodiment provides a method for preparing a dual cation positive electrode material, comprising the following steps: 1) Prepare 10% thiophene aqueous solution and 1 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.8 V, and the electrolysis time was 5 hours to obtain H3PW 12 O 40 of heteropoly blue solution; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 1:2, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing for 8 days; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 1:2, and the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 2:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding 15% permanganate to the mixture in step 4) while stirring, and placing the mixture at 180° C. for reaction for 24 hours after the addition is completed; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0015] Example 3 This embodiment provides a method for preparing a dual cation positive electrode material, comprising the following steps: 1) Prepare 8% pyrrole aqueous solution and 0.8 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.6 V, and the electrolysis time was 4 hours to obtain H3PW 12 O 40 of heteropoly blue solution; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 1:1, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing for 10 days; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 1:1, and the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 2.5:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) dichromic acid with a mass concentration of 13% was added dropwise to the mixture in step 4) during stirring, and after the addition was completed, the mixture was placed in an environment of 160° C. for reaction for 20 hours; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0016] Example 4 The difference between this embodiment and embodiment 1 is that in this embodiment, the conductive polymer monomer in step 1) is a mixture of aniline and pyrrole; the remaining steps are the same as those in embodiment 1.
[0017] This embodiment provides a method for preparing a dual cation positive electrode material, comprising the following steps: 1) Prepare a 5% aqueous solution of a mixture of aniline and pyrrole and a 0.5 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.5 V, and the electrolysis time was 3 hours to obtain H3PW 12 O 40of heteropoly blue solution; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 2:1, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing for 7 days; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 2:1, and the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 1.5:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess of 10% diluted nitric acid to the mixture in step 4) during stirring, and placing the mixture at 140° C. for reaction for 16 hours after the addition is completed; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0018] Example 5 The difference between this embodiment and embodiment 1 is that in this embodiment, the heteropoly acid in step 3) is H3PMO 12 O 40 , the remaining steps are the same as those in Example 1.
[0019] This embodiment provides a method for preparing a dual cation positive electrode material, comprising the following steps: 1) Prepare aniline aqueous solution with a mass concentration of 5% and H3PMO with a molar concentration of 0.5 mol / L. 12 O 40 Aqueous solution; 2) Add the H3PMO described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.5 V, and the electrolysis time was 3 hours to obtain H3PMO 12 O 40 of heteropoly blue solution; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 2:1, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing for 7 days; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 2:1, and the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 1.5:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess of 10% diluted nitric acid to the mixture in step 4) during stirring, and placing the mixture at 140° C. for reaction for 16 hours after the addition is completed; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0020] Comparative Example 1 In this comparative example, the positive electrode material was prepared by the following steps: 1) Prepare 5% aniline aqueous solution and 0.5 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.5 V, and the electrolysis time was 3 hours to obtain H3PW 12 O 40 of heteropoly blue solution; 3) Adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 2:1, reacting to generate heteropoly blue lithium sodium, wherein the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 2:1, and the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 1.5:1; separating the precipitated heteropoly blue lithium sodium crystals after standing for 7 days to obtain a positive electrode material free of conductive polymer.
[0021] The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0022] Comparative Example 2 In this comparative example, the positive electrode material was prepared by the following steps: 1) Prepare 5% aniline aqueous solution and 0.5 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.5 V, and the electrolysis time was 3 hours to obtain H3PW 12 O 40 of heteropoly blue solution; 3) adding Na2CO3 to the heteropoly blue solution in step 2) to react and generate heteropoly blue sodium, and separating the precipitated heteropoly blue sodium crystals after standing for 7 days; the molar ratio of Na2CO3 to heteropoly acid is 1.5:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess of 10% diluted nitric acid to the mixture in step 4) during stirring, and placing the mixture at 140° C. for reaction for 16 hours after the addition is completed; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0023] Comparative Example 3 In this comparative example, the positive electrode material was prepared by the following steps: 1) Prepare 5% aniline aqueous solution and 0.5 mol / L H3PW 12 O 40 Aqueous solution; 2) Place the H3PW described in step 1) 12 O 40 The aqueous solution was electrolyzed, the cathode potential was controlled at -0.5 V, and the electrolysis time was 3 hours to obtain H3PW 12 O 40 of heteropoly blue solution; 3) adding Li2CO3 to the heteropoly blue solution in step 2) to react and generate heteropoly blue lithium, and separating and precipitating heteropoly blue lithium crystals after standing for 7 days; the molar ratio of Li2CO3 to heteropoly acid is 1.5:1; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess of 10% diluted nitric acid to the mixture in step 4) during stirring, and placing the mixture at 140° C. for reaction for 16 hours after the addition is completed; 6) Separate the solid matter after the hydrothermal reaction, rinse it repeatedly with deionized water, and dry it to obtain a dual-cationic positive electrode material; The obtained positive electrode material was prepared into a button cell by a button cell process and tested.
[0024] The test results of Examples 1-5 and Comparative Examples 1-3 of the present invention are shown in Table 1.
[0025] Table 1 Test results of Examples 1-5 and Comparative Examples 1-3 From the data in the table, it can be seen that Examples 1-5 contain conductive polymers and heteropoly blue. At a discharge rate of 2C, the gram capacity is well maintained, and the conductive polymer has a porous structure. After 50 cycles, the capacity retention rate is still above 96%; Comparative Example 1 does not contain a conductive polymer, and the electron transport capability of the positive electrode material prepared in this example is affected, the gram capacity is poor, and the rate characteristics and cycle characteristics are not good.
[0026] Comparative Example 2 does not contain lithium ions but only sodium ions. The ion transport capacity of the positive electrode material is affected, the gram capacity is small, and the rate performance and cycle characteristics are also poor.
[0027] Comparative Example 3 does not contain sodium ions but only lithium ions. In the pores of sodium ions with a large radius that can originally accommodate a larger number of lithium ions, the gram capacity is larger than that of Example 1, and the cycle performance is the same as that of Example 1. However, lithium-ion batteries cannot be compared with dual-cation positive electrode materials due to defects such as resource limitations and poor safety after enlargement.
[0028] H3PW in Example 2 12 O 40 The molar concentration of the aqueous solution is relatively high, and more heteropoly blue is produced after electrolysis. When it encounters an oxidizing acid later, it is oxidized by the oxidizing acid and converted back into heteropoly acid, which affects the pore structure of the conductive polymer. Therefore, compared with Example 1, the gram capacity is lower; H3PW in Example 2 12 O 40 The molar concentration of the aqueous solution is consistent with that of Example 1, so the gram capacity is similar to that of Example 1; the polymer monomer in Example 4 is a mixture of aniline and pyrrole, both of which are oxidatively polymerized at the same time. It may be that due to the inconsistency of the pore sizes, the phenomenon of small pores blocking large pores occurs, resulting in a decrease in gram capacity; H3PMO used in Example 5 12 O 40 , characteristics and H3PW 12 O 40 Therefore, the gram capacity and rate characteristics are not much different from those in Example 1.
[0029] The reason why the conductive polymer has a porous structure is that dilute nitric acid reacts with carbonate ions in the solution during the addition process to produce carbon dioxide. The carbon dioxide causes the conductive polymer to form a porous structure during the overflow process. The porous structure is more conducive to the transmission of cations due to its abundant pores, which can increase the transmission rate of cations in the positive electrode material.
[0030] Comparative Example 1 does not contain a conductive polymer, and thus does not have a porous structure of a conductive polymer. Although the polyblue salt has pores, they are not as abundant as the pores superimposed with the conductive polymer. The number of pores is small, and the number of cations that can be accommodated is also small, resulting in a decrease in gram capacity. The small number of pores will also cause the cation transport to be blocked, the internal resistance to increase, the rate characteristics to decrease, and the cycle characteristics to be poor.
[0031] Comparative Example 2 does not contain lithium ions but only sodium ions. Since the radius of sodium ions is larger than that of lithium ions, in the original pore structure, the pores that can accommodate and transport lithium ions may not be able to accommodate and transport sodium ions. Therefore, the number of cations that can be accommodated is also less, and the gram capacity decreases. Compared with sodium ions, the pores are smaller, the transport is hindered, the internal resistance increases, the rate decreases, and the cycle performance decreases.
[0032] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A method for preparing a dual cation positive electrode material, characterized in that: The steps include: 1) preparing a conductive polymer monomer aqueous solution and a heteropoly acid aqueous solution; 2) electrolyzing the heteropoly acid aqueous solution in step 1) to obtain a heteropoly blue solution of heteropoly acid; 3) adding Li2CO3 and Na2CO3 to the heteropoly blue solution in step 2), wherein the ratio of Li2CO3 to Na2CO3 is 1:0.5-2, reacting to generate heteropoly blue lithium sodium, and separating the precipitated heteropoly blue lithium sodium crystals after standing; the ratio of lithium to sodium in the heteropoly blue lithium sodium crystals is 1:0.5-2; 4) adding the crystals in step 3) to the aqueous solution of the conductive polymer monomer prepared in step 1) to obtain a mixture; 5) adding an excess amount of a strong oxidizing acid solution to the mixture in step 4) while stirring, and reacting the mixture at 140°C-180°C for 16h-24h after the addition is complete; 6) The solid matter after the hydrothermal reaction is separated, repeatedly rinsed with deionized water, and dried to obtain a dual-cationic positive electrode material.
2. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: The mass concentration of the conductive polymer monomer aqueous solution in step 1) is 5%-10%.
3. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: In step 1) H3PW 12 O 40 The molar concentration of the aqueous solution is 0.5 mol / L-1 mol / L.
4. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: In the step 1), the conductive polymer monomer is one or more of aniline, thiophene and pyrrole.
5. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: The electrolysis conditions in step 2) are as follows: the cathode potential is -0.5V to -0.8V, and the electrolysis time is 3-5 hours.
6. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: In step 3), the heteropoly acid is H3PW 12 O 40 or H3PMO 12 O 40 .
7. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: In the step 3), the molar ratio of Li2CO3 plus Na2CO3 to heteropoly acid is 1.5-2.5:
1.
8. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: The standing time in step 3) is 7-10 days.
9. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: The strong oxidizing acid in step 5) is nitric acid.
10. The method for preparing the dual cation positive electrode material according to claim 1, characterized in that: The mass concentration of the strong oxidizing acid dilute solution in step 5) is 10%-15%.
Citation Information
Patent Citations
Positive electrode active material, positive plate comprising positive electrode active material and mixed lithium-sodium ion battery
CN116741945A
Cited By
High-performance sulfonated polyaryletherketone sulfone / heteropolyblue composite proton exchange membrane and preparation method thereof
CN121495351A